Tidal deformations observed at the Vyhne tidal station - BRIMICH, Ladislav (Contributions to Geophysics and Geodesy, 2021)
In the paper the results of the extensometric measurements obtained by two different methods are presented. From the comparison of the different time series of extensometric data, we can conclude that the observed amplitudes and phase differences of the main tidal waves are at the Vyhne tidal station extraordinary stable